The Relationship between Physical Literacy and Physical Fitness in Physical Education in Senior Schools in the City of Bandung - Farizan Fathul Hakim; Yudy Hendrayana; Marisa Noviyanti Fajrah Ilsya (Universitas Negeri Semarang, 2025)
This study aims to analyze the relationship between physical literacy and physical fitness in physical education learning in grade XI high school students throughout the city of Bandung. The research uses a quantitative method with a correlational approach. The research subjects amounted to 324 students who were selected through cluster random sampling techniques from three State High Schools in the city of Bandung. Physical literacy was measured using the Physical Literacy Assessment of Youth (PLAY) instrument, while physical fitness was measured using the Nusantara Student Fitness Test (TKPN). Data analysis includes instrument validity and reliability tests, descriptive analysis, Pearson correlation tests, and simple linear regression analysis. The results showed that the level of physical literacy of students was in the medium category and there was a positive and significant relationship between physical literacy and physical fitness (p < 0.05), although the strength of the relationship was relatively low. Regression analysis shows that physical literacy contributes significantly to students' physical fitness. The conclusion of this study shows that physical literacy has an important role in supporting students' physical fitness, so strengthening physical literacy needs to be systematically integrated in physical education learning in schools.